Finite-time guaranteed cost control for stochastic nonlinear switched systems with time-varying delays and reaction-diffusion. Issue 5 (4th May 2023) - Gokulakrishnan, V.; Srinivasan, R.; Syed Ali, M.; Rajchakit, Grienggrai
Abstract : This study considers the finite-time guaranteed cost control problem for a class of stochastic nonlinear switched systems (SNSSs) with time-varying delays, reaction-diffusion and actuator faults. The reliable control strategy is designed to finite-time stabilization for SNSSs. By virtue of the Lyapunov method, Neumann boundary condition, some famous inequality techniques and average dwell-time approach, sufficient criterion are obtained to ensure finite-time stability of proposed controlled systems. We investigate the finite-time stabilization results by designing the control gain matrices for reliable controller. The sufficient criteria are expressed in terms of linear matrix inequalities (LMIs) that can be verified by MATLAB LMI toolbox. Furthermore, a new sufficient criterion is presented to guarantee the finite-time cost control of proposed controlled systems. Based on this criterion, the effects of control gains, switching signals and time-varying delays on finite-time stability are also analysed. At last, numerical simulations are presented to illustrate the efficiency and superiority of designed reliable controller.